Study on Mechanical Properties and Fire Resistance of Epoxy Nanocomposite Reinforced with Environmentally Friendly Additive: Nanoclay I.30E - Tuan Anh Nguyen; Thi Mai Huong Pham; Thi Huong Dang; Thi Hanh Do; Quang Tung Nguyen (Journal of Chemistry)
The main purpose of this study is to complete the research process of dispersing nanoclay I.30E (montmorillonite) into epoxy Epikote 240 by mechanical method combined with energy-saving ultrasonic method. We investigate appropriate dispersion conditions such as stirring speed, mechanical stirring temperature, ultrasonic stirring time, and ultrasonic stirring capacity, which affect the mechanical properties and fire resistance of nanocomposite materials. The nanoclay contents studied were 1, 2, 3, and 4% by weight, and the methods used in this study are FE-SEM; XRD; and flame-retardant evaluation methods: LOI, UL 94HB. The mechanical properties were studied: tensile strength, flexural strength, compression strength, and impact resistance Izod. The dispersion method was recommended to stir mechanically at a speed of 3000 rpm at 80°C for 8 hours and then conduct ultrasonic vibrations for 6 hours at 65°C. The results showed that epoxy Epikote 240/nanoclay I.30E nanocomposite material had mechanical properties and improved fire retardancy with a small amount of nanoclay I.30E added (2% by weight): tensile strength of 63.5 MPa (increased by 13.59%), flexural strength of 116.80 MPa (increased by 34.63%), compressive strength of 179.67 MPa (increased by 15.11%), impact resistance Izod of 12.81 KJ/m2 (increased by 80.16%), oxygen limit of 23.7%, and combustion rate of 24.5 mm/min; according to UL 94HB, the combustion rate reached 22.59 mm/min.